A Point Mutation in the Iron-Responsive Element of the L-Ferritin in a Family with Hereditary Hyperferritinemia Cataract Syndrome - Karen Wong; Yousef Barbin; Subrata Chakrabarti; Paul Adams (Canadian Journal of Gastroenterology)
BACKGROUND: Hereditary hyperferritinemia cataract syndrome is an autosomal dominant condition that is characterized by a high serum ferritin level and bilateral early-onset cataracts in the absence of iron overload. The genetic abnormality is identified as a mutation in the 5' regulatory region of the L-ferritin messenger RNA known as the iron-responsive element (IRE). The IRE controls ferritin synthesis in response to cytoplasmic iron pools by interacting with regulatory proteins called iron responsive proteins. Mutations in the IRE decrease its affinity for iron responsive proteins, leading to the constitutive synthesis of L-ferritin which results in hyperferritinemia and the intracellular accumulation of ferritin in the lens and eventual cataract formation.